2009
DOI: 10.1524/ract.2009.1571
|View full text |Cite
|
Sign up to set email alerts
|

Activity standardization of 41Ca by means of liquid scintillation counting

Abstract: Liquid scintillation counting according to the CIEMAT/NIST method was used for the activity standardization of 41 Ca. The counting efficiencies were computed with two different atomic rearrangement models (KLM and KL 1 L 2 L 3 M) applying an improved model for the interaction of low-energy X-rays with the scintillation cocktail. This report comprises a detailed description of the determination of nuclear and atomic input data, sample preparation as well as a comprehensive uncertainty analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Whereas determinations reported in literature rely on parameters with large uncertainties such as neutron capture cross section (yielding the number of 41 Ca atoms), X-ray fluorescence yield (calculation of activity) and self absorption of X-ray samples (experimental data for activity), the work reported here applies methodologies and parameters which are known to have very small uncertainties. Compared to the previous report by Kossert et al (2009), the chemical procedure has been improved, yielding LSC samples of higher 41 Ca/Ca ratio with much lower content of both radioactive and non-radioactive impurities. The precision and accuracy of the activity determination by LSC was considerably improved by replacing the CIEMAT/NIST efficiency tracing method with the TDCR technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas determinations reported in literature rely on parameters with large uncertainties such as neutron capture cross section (yielding the number of 41 Ca atoms), X-ray fluorescence yield (calculation of activity) and self absorption of X-ray samples (experimental data for activity), the work reported here applies methodologies and parameters which are known to have very small uncertainties. Compared to the previous report by Kossert et al (2009), the chemical procedure has been improved, yielding LSC samples of higher 41 Ca/Ca ratio with much lower content of both radioactive and non-radioactive impurities. The precision and accuracy of the activity determination by LSC was considerably improved by replacing the CIEMAT/NIST efficiency tracing method with the TDCR technique.…”
Section: Resultsmentioning
confidence: 99%
“…h A complete report of the study tentatively described by Kutschera et al (1989). i A recalculation by Kossert et al (2009) the half-life by re-evaluating the data reported earlier and coming up with substantially larger values for the half-life. Klein et al (1991) opted for an interesting alternative to determine the half-life of 41 Ca by linking content and activity to 36 Cl in Antarctic meteorites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation